Development Of New Protocols To Evaluate The Transverse Loading Of Mine Ventilation Stoppings - T. M. Barczak; T. J. Batchler (The National Institute for Occupational Safety and Health (NIOSH))
The Code of Federal Regulations (CFR) requires that the transverse load capacity of stoppings be equal to or greater than traditionally accepted in mine controls, which for block stoppings is generally accepted as 39 psf as referenced in the preamble to the CFR standard. This measure is based on physical testing of a freestanding wall in accordance with ASTM E 72 specifications, where our past research has shown that the dominant parameter is the tensile strength of the sealant. A new protocol based on rigid arch loading of the structure is proposed to determine the true transverse load capacity of block stoppings. Arching is achieved by the restraint of the stopping against the mine roof and floor, whereby compressive forces are developed within the wall. A laboratory procedure using the NIOSH Mine Roof Simulator (MRS) to simulate rigid arching of block stoppings was developed and results verified through full-scale in-mine tests. The rigid arch tests have demonstrated transverse load capacities more than an order of magnitude higher than the ASTM E 72 evaluation method from which the 39-psf requirement is derived. More importantly, the rigid arch tests have shown that the load capability is dependent on the physical properties of the block and geometric properties of the wall and not the sealant.